Pengembangan E-Book Mata Kuliah Drama sebagai Media Pembelajaran Mandiri di Masa Pandemi - Liza Septa Wilyanti; Larlen Larlen; Irma Suryani (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This research aims to develop an eBook of Drama courses that can be used independently by students by linking learning videos that have been uploaded by lecturers in youtube media. The development of drama e-book courses aims to help and support distance learning, especially during this pandemic. This research follows the steps of ADDIE (analize, design, develop, implement, and evaluate) which focuses on development research. Based on the results of data analysis, the average value of each aspect tested in the eBook of this Drama course is 83.85. This figure shows the teaching book on Drama Subjects is feasible and valid to use. The effectiveness and practicality of the e-book drama courses that have been used obtained an average score of 83.25. This figure shows the Drama course eBook is practical and effective for use in learning.